2017
DOI: 10.1103/physrevb.95.144407
|View full text |Cite
|
Sign up to set email alerts
|

Competing spin density wave, collinear, and helical magnetism inFe1+xTe

Abstract: The Fe 1+x Te phase diagram consists of two distinct magnetic structures with collinear order present at low interstitial iron concentrations and a helical phase at large values of x with these phases separated by a Lifshitz point. We use unpolarized single-crystal diffraction to confirm the helical phase for large interstitial iron concentrations and polarized single-crystal diffraction to demonstrate the collinear order for the iron-deficient side of the Fe 1+x Te phase diagram. Polarized neutron inelastic s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 103 publications
(191 reference statements)
3
23
1
Order By: Relevance
“…Extending INS to polarized neutron measurements offers a robust perspective offering the possibility to explore directly and unambiguously the spinphonon coupling picture in iron telluride. In this context, the anisotropic nature of different types of low-temperature magnetic fluctuations were probed in iron telluride Fe1+xTe [60], confirming further the importance of magnetoelastic coupling. A next step could be the use of this same technique to draw a complete picture of both the lattice and the spin components in these materials.…”
Section: Discussionsupporting
confidence: 57%
“…Extending INS to polarized neutron measurements offers a robust perspective offering the possibility to explore directly and unambiguously the spinphonon coupling picture in iron telluride. In this context, the anisotropic nature of different types of low-temperature magnetic fluctuations were probed in iron telluride Fe1+xTe [60], confirming further the importance of magnetoelastic coupling. A next step could be the use of this same technique to draw a complete picture of both the lattice and the spin components in these materials.…”
Section: Discussionsupporting
confidence: 57%
“…The low‐temperature Mössbauer spectrum of the Fe 1.05 Te system consisted of four magnetic sextets, which were a consequence of four iron ion groups . For the Fe 1.125 Te system, a more complex low temperature spectrum is expected because of the presence of spin density waves . It was reported that the magnetic structure of Fe 1.124(5) Te (notations of ref.…”
Section: Resultsmentioning
confidence: 99%
“…It was reported that the magnetic structure of Fe 1.124(5) Te (notations of ref. ) is a collinear spin density wave (SDW) phase with incommensurate wave‐vector q = 0.46 ± 0.01 (in reciprocal‐lattice units (r.l.u. )) along [ H ,0,0] direction (that corresponds to the x ‐direction in real space).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations